Effect of Disinfection on the Bond Strength between Denture Teeth and Microwave-Cured Acrylic Resin Denture Base - Matos, Adaias O.; Costa, Josiane O.; Beline, Thamara; Ogawa, Erika S.; Assunção, Wirley G. [UNESP]; Mesquita, Marcelo F.; Consani, Rafael X.; Barão, Valentim A. (Wiley, 2018)
Purpose: Denture tooth debonding is a common complication for denture wearers; however, the effect of complete denture disinfection on bonding between denture teeth and acrylic resin remains unclear. The aim of this study was to evaluate the effect of disinfection methods on the bond strength between denture teeth and microwave-cured acrylic resin denture base. Materials and Methods: Three commercial brands of denture teeth (Trilux, Biolux, Vipi Dent Plus) and one microwave-cured acrylic resin denture base were tested. Each brand of denture teeth was divided into seven groups (n = 6; estimated by partial Eta squared). The specimenss of groups H and Cl were immersed in 1% sodium hypochlorite and 4% chlorhexidine digluconate for 7 days, respectively. In group Br, the specimens were subjected to toothbrush simulation under 200 g of force for 20,000 cycles. In groups Br-H and Br-Cl, the specimens were brushed and further disinfected with 1% sodium hypochlorite and 4% chlorhexidine digluconate, respectively. In control groups 1 (Co1) and 2 (Co2), the specimens were stored in distilled water for 50 ± 2 hours and 7 days, respectively. Shear bond strength testing was performed at the resin/tooth interface in a universal testing machine at a 1 mm/min crosshead speed. The failure pattern was quantified and classified into adhesive, cohesive, or mixed. Data were analyzed using two-way ANOVA and Tukey HSD test (α = 0.05). Results: Disinfection with 1% sodium hypochlorite (p = 0.031), brushing (p < 0.0001), and association of brushing with either 1% sodium hypochlorite (p < 0.0001) or 4% chlorhexidine digluconate (p = 0.01) reduced the bond strength between denture teeth and microwave-cured acrylic resin denture base. All commercial brands of denture teeth presented a similar bond strength (p > 0.05). The failure pattern was predominantly adhesive independent of the disinfection method and denture tooth brand. Conclusions: Disinfection with sodium hypochlorite, brushing, and the association of mechanical and chemical methods reduced the bond strength between denture tooth and microwave-cured acrylic resin denture base.
Keywords: chlorhexidine digluconate; Removable denture; sodium hypochlorite; toothbrushing